2017
DOI: 10.1038/onc.2017.283
|View full text |Cite
|
Sign up to set email alerts
|

S100A7: from mechanism to cancer therapy

Abstract: Within the tumor, malignant and stromal cells support each other by secreting a wide variety of growth factors and cytokines, allowing tumor growth and disease progression. The identification and regulation of those key factors in this crosstalk has opened the opportunity to develop new therapeutic strategies that not only act on the tumor cells but also on the stroma. Among these factors, S100A7 protein has gained interest in the last years. With key roles in cell motility its expression correlates with incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 42 publications
1
32
0
Order By: Relevance
“…A role for S100A7 in the formation of premetastatic niches has been recently identified. S100A7 secreted by tumor cells transforms surrounding stromal cells, making them secrete numerous growth factors which, in turn, support the establishment of aggressive milieu to support tumor progression and facilitate metastatic spread (45). Celltype-specific exosome integrin uptake could activate Src signaling and promote several proinflammatory S100 genes up-regulation in lung fibroblast cells, including S100A16, which implicated in facilitating lung metastasis (38).…”
Section: Discussionmentioning
confidence: 99%
“…A role for S100A7 in the formation of premetastatic niches has been recently identified. S100A7 secreted by tumor cells transforms surrounding stromal cells, making them secrete numerous growth factors which, in turn, support the establishment of aggressive milieu to support tumor progression and facilitate metastatic spread (45). Celltype-specific exosome integrin uptake could activate Src signaling and promote several proinflammatory S100 genes up-regulation in lung fibroblast cells, including S100A16, which implicated in facilitating lung metastasis (38).…”
Section: Discussionmentioning
confidence: 99%
“…Antibodies 6B12 S100A4 Binds extracellular S100A4 and thereby acts as an immunomodulating agent Pre-clinical [232,233] 5C3 S100A4 Binds to and neutralises S100A4 Pre-clinical [234] 6F5 S100A7 Binds to S100A7 and thereby blocks S100A7/RAGE interaction Pre-clinical [235] Ab45 S100A8/S100A9…”
Section: Inhibitor S100 Target Mechanism Of Action Current Status Refmentioning
confidence: 99%
“…Furthermore, a monoclonal antibody targeting extracellular S100A7 was designed. It could be demonstrated that this anti-S100A7 antibody, named 6F5, blocks S100A7/RAGE interaction, thereby inhibiting S100A7-mediated MMP9 activity, leading to decreased tumour growth, cell migration, and angiogenesis in a xenograft cancer model [235]. In terms of neutralising the DAMP molecules S100A8 and S100A9, monoclonal Ab45 was identified to be the most selective among ten anti-S100A8/S100A9 antibodies.…”
Section: Neutralising Antibodiesmentioning
confidence: 99%
“…A total of 216 DEPs were identified, and then GO analysis and systematic pathway-based enrichment analysis was performed. Among the DEPs, many have been reported or predicted as potential targets for cancer antiangiogenic treatment (see Figure 1D and Supplementary Table S4), such as FBLN5 (Albig & Schiemann, 2004), CEACAM6 (Zang et al , 2015), S100A9 (Eisenblaetter et al , 2017; Zhang et al , 2017), THBS1 (Lawler, 2002), CANX (Demeure et al , 2016), TNC (Kawamura et al , 2018), HSP47 (Wu et al , 2016), CTTN (Ramos-Garcia & Gonzalez-Moles, 2018), MMP9 (Gupta et al , 2013), TGM2 (Lei et al , 2018), S100A7 (Padilla et al , 2017), LCN2 (Hu et al , 2018), RACK1 (Wang et al , 2011), PGK1 (Shichijo et al , 2004), EPO (Samoszuk et al , 1996), CD74 (Gai et al , 2018), GRP78 (Kao et al , 2018). For these candidate antiangiogenic targets, our results are consistent with previously published data.…”
Section: Discussionmentioning
confidence: 99%